VOICE OF CUSTOMER TENTANG STUDENT CENTER UNIVERSITAS KRISTEN PETRA - Connie Susilawati (Civil Engineering Dimension, 2002)
Petra Christian University plans to build a Student Center, which functions as a place for students to gather in an informal meeting, a place for student activities, and a place with social and cultural facilities for students, but still fit with the purpose of the university. To prepare a more suitable plan for the students as the main users, their voices should be considered. A survey to 1087 students has been done to gather their voices. This study evaluates level of need and level of importance of the room that will be provided in the Student Centre. The level of satisfaction of the existing facilities’ size has been evaluated to the student guild. This study has recommended rooms under seven categories which have to be provided, such as: rooms for student union, academic support, administration, social, religious rooms, commercial room and some complementary rooms Abstract in Bahasa Indonesia : Universitas Kristen Petra merencanakan untuk mendirikan Student Center yang merupakan tempat berkumpulnya mahasiswa dan sivitas akademika dalam pertemuan informal, tempat aktivitas mahasiswa dan tempat yang menyediakan fasilitas rekreasi, sosial, dan kultural sesuai dengan dasar dan tujuan universitas. Agar perencanaanya lebih sesuai dengan kebutuhan pengguna utamanya, yaitu mahasiswa, maka pendapat mereka perlu menjadi bahan pertimbangan. Untuk mengetahui pendapat mahasiswa telah dilakukan survey kepada 1087 responden mahasiswa aktifis dan non aktifis. Studi ini menilai tingkat kebutuhan dan tingkat kepentingan dari ruangan yang akan disediakan di dalam Student Center tersebut. Mengingat sebagian ruangan-ruangan tersebut sudah ada, maka dilakukan juga evaluasi kepuasan pengguna ruangan terhadap luas ruangan yang diwakili oleh aktivis mahasiswa. Hasil akhir dari penelitian ini adalah rekomendasi ruangan yang perlu disediakan dapat dikategorikan sebagai ruangan untuk organisasi mahasiswa, ruang penunjang akademik, ruang spriritual, ruang administrasi, ruang sosial dan dilengkapi dengan beberapa ruang komersial serta ruang pelengkap.